Correction: Correction: Semaphorin 3D inhibits proliferation and migration of papillary thyroid carcinoma by regulating MAPK/ERK signaling pathway - Rui Hai; Qian You; Fei Wu; Guochun Qiu Qian; Yang Liang; Shu Linjun Xie; Xiangyu Zhou; Guochun Qiu; Qian Yang; Liang Shu; Linjun Xie (Molecular Biology Reports, 2026)

Correction: Semaphorin 3D inhibits proliferation and migration of papillary thyroid carcinoma by regulating MAPK/ERK signaling pathway - Rui Hai; Qian You; Fei Wu; Guochun Qiu; Qian Yang; Liang Shu; Linjun Xie; Xiangyu Zhou (Molecular Biology Reports, 2026)

Integrated network toxicology, transcriptomics, and metabolomics revealed the potential mechanisms of aluminum-induced testicular injury - Siyu Liao; Liqing Huang; Yusi Zhou; Xin Zhang; Shaofeng Huang; Linjun Yu; Shiman Zhu; Wei Chen; Rong Wang; Haimei Qin (Food and Chemical Toxicology, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

An overview of the formation mechanism characteristics of glacial lake outburst floods in Tibet, China - Jiankang Liu; Ruilin Xu; Linjun Zhou; Ting Yi; Jianxun Liu; Jiajia Zhang; Bo Gao; Yuanling Li; Hai Huang (Natural Hazards, 2026)

Highly efficient hydrogen production via photothermal-catalytic methanol steam reforming over high-entropy metal oxides - Xingyu Yin; Linjun Tang; Zhiwei Zhan; Chun Zhu; Jingtai Zhang; Xiaoxiang Zhou; Shaohua Chen; Chuanyun Yang; Ling Li; Tetsuya Kako; Jinhua Ye; Shangbo Ning (Science Bulletin, 2026)

In situ ammonia recovery relieves ammonia stress in anaerobic digestion and multi-omics elucidate community-dominant and functionally dominant genera of methanogens - Linjun Wu; Huan Li; Yanyue Gu; Yuexi Zhou; Zhiqiang Shen; Jiane Zuo (Bioresource Technology, 2026)

Preparation process and performance study of transparent veneer treated with three metal salt-based deep eutectic solvent (MDES) - Yanbing Zhang; Xilin Zhou; Jingtai Zhang; Caixia Liu; Huihui Liu; Ruocai Bai; Siyi He; Linjun Zhong; Yan Wu (Biomass and Bioenergy, 2026)

Using SBAS-InSAR and audio-magnetotelluric sounding to characterize two-dimensional deformation and failure mechanisms in mining-induced landslides: a case study from Leji - Yifei Zhu; Chunxi Hu; Zhenkai Zhou; Xin Yao; Yong Wei; Zhen Lu; Linjun Wang; Xiajun Liu; Di Wang; Jiaxin Wu (Landslides, 2026)

A new quest for green finance and ESG excellence: A new perspective on energy efficiency - Linjun Cao; Nan Zhou; Mo Chen; Yingrong Zheng (Journal of Environmental Management, 2026)

Iron-driven synergism among microbial functional taxa facilitates recovery from denitrification toxicity - Yongzhi Zhang; Xiaoxiao Li; Linjun Gao; Ping Ye; Rui Wang; En Zhou; Tian Sun; Miaoqing Xu; Rui Wan; Xiang Li (Journal of Environmental Management, 2026)

Enhancing anaerobic treatment of crotonaldehyde manufacture wastewater through anaerobic granular sludge supplemented with activated carbon: Performance, microbial activity and microbial metabolic function - Tao Liu; Zhiying Yan; Linjun Wu; Yuexi Zhou; Jiane Zuo (Process Safety and Environmental Protection, 2025)

Combined effects of high-fat diet feeding and Streptococcus agalactiae infection on lipid metabolism, antioxidant status, and immune response in tilapia (Oreochromis niloticus) - Rui Jia; Yiran Hou; Linjun Zhou; Chengfeng Zhang; Bing Li; Jian Zhu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Integrating dual-stage gas permeable membranes and humic acid recovery to optimize fenton oxidation of landfill leachate: Insights into full-process performance and DOM molecular-level transformation - Linjun Wu; Huan Li; Yanyue Gu; Zhiqiang Shen; Yuexi Zhou; Jiane Zuo (Water Research, 2025)

Alterations in microbial-mediated methane, nitrogen, sulfur, and phosphorus cycling within paddy soil induced by integrated rice-fish farming - Yiran Hou; Rui Jia; Linjun Zhou; Liqiang Zhang; Sun Wei; Bing Li; Jian Zhu (Journal of Environmental Management, 2025)

Independent of alkalinity addition: Ammonia recovery via gas permeable membranes driven by self-sustained alkalinity in anaerobic digestate with low-rate aeration - Linjun Wu; Huan Li; Yuexi Zhou; Zhiqiang Shen; Jiane Zuo (Journal of Water Process Engineering, 2025)

Integrated rice-fish farming dynamically altered the metal resistances and microbial-mediated iron, arsenic, and mercury biotransformation in paddy soil - Yiran Hou; Rui Jia; Linjun Zhou; Liqiang Zhang; Wei Sun; Bing Li; Jian Zhu (Environmental Pollution, 2025)

Microplastics as vectors for antibiotic resistance: Role of pathogens, heavy metals, and pharmaceuticals and personal care products - Linjun Wu; Jiao Dong; Zhiqiang Shen; Yuexi Zhou (Journal of Water Process Engineering, 2024)

Dynamic intrauterine crosstalk promotes porcine embryo implantation during early pregnancy - Xupeng Zang; Shengchen Gu; Wenjing Wang; Junsong Shi; Jianyu Gan; Qun Hu; Chen Zhou; Yue Ding; Yanjuan He; Lei Jiang; Ting Gu; Zheng Xu; et al. (Science China Life Sciences, 2024)

Fe-doped CeTiOx catalysts facilitate the oriented oxidation of NO to achieving simultaneous desulfurization and denitration in a WFGD system - Lei Zhou; Zhixiang Wei; Junkang Fan; Qingqing Yu; Chuang Zhao; Jie Zhang; Liming Yang; Weili Dai; Linjun Yang (Fuel, 2024)

Species distribution modeling combined with environmental DNA analysis to explore distribution of invasive alien mosquitofish (Gambusia affinis) in China - Xu Han; Jinxiao Chen; Lang Wu; Guo Zhang; Xiaoteng Fan; Tao Yan; Long Zhu; Yongjing Guan; Linjun Zhou; Tingting Hou; Xue Xue; Xiangju Li; et al. (Environmental Science and Pollution Research, 2024)

Ammonia recovery from landfill leachate using gas-permeable membranes: Comparison of membrane fibers and expanded membrane tubes in both in-situ and shell-tube configurations - Linjun Wu; Zhiqiang Shen; Yuexi Zhou; Jiane Zuo (Chemical Engineering Journal, 2024)

Mechanistic insights into the leaching and environmental safety of arsenic in ceramsite prepared from fly ash - Bing Song; Zequan Liu; Chengming Li; Shiji Zhou; Linjun Yang; Zhiliang Chen; Min Song (Chemosphere, 2023)

Stimulating anaerobic digestion to degrade recalcitrant organic pollutants: Potential role of conductive materials-led direct interspecies electron transfer - Linjun Wu; Zhiqiang Shen; Yuexi Zhou; Jiane Zuo (Journal of Environmental Management, 2023)

Competitive adsorption characteristics of VOCs and water vapor by activated carbon prepared from Fe/N-doped pistachio shell - Tangying Cheng; Jinjin Li; Xiuwei Ma; Linjun Yang; Lei Zhou; Hao Wu (Environmental Science and Pollution Research, 2023)

Transcriptome-wide profiling of RNA N4-cytidine acetylation in Arabidopsis thaliana and Oryza sativa - Bin Li; Donghao Li; Linjun Cai; Qiting Zhou; Cong Liu; Jianzhong Lin; Yixing Li; Xiaoying Zhao; Li Li; Xuanming Liu; Chongsheng He (Molecular Plant, 2023)

Field-realistic dose of cefotaxime enhances potential mobility of β-lactam resistance genes in the gut microbiota of zebrafish (Danio rerio) - Xue Xue; Xiangju Li; Jialin Liu; Long Zhu; Linjun Zhou; Jia Jia; Zaizhao Wang (Aquatic Toxicology, 2023)

Release and migration of Hg during desulfurization wastewater evaporation process: Whole process evaluation by experimental and theoretical study - Heng Chen; Lingxiao Zhan; Hao Zhou; Zhihao Li; Jiawei Chen; Zongkang Sun; Hao Wu; Linjun Yang (Journal of Hazardous Materials, 2023)

Nitrogen-doped porous biochar for selective adsorption of toluene under humid conditions - Tangying Cheng; Ye Bian; Jinjin Li; Xiuwei Ma; Linjun Yang; Lei Zhou; Hao Wu (Fuel, 2023)

Conductive materials as fantastic toolkits to stimulate direct interspecies electron transfer in anaerobic digestion: new insights into methanogenesis contribution, characterization technology, and downstream treatment - Linjun Wu; Tao Jin; Hong Chen; Zhiqiang Shen; Yuexi Zhou (Journal of Environmental Management, 2023)

Concentration of desulfurization wastewater using low-temperature flue gas and associated corrosion risk - Hao Zhou; Lingxiao Zhan; Heng Chen; Linjun Yang (Environmental Science and Pollution Research, 2022)

Semaphorin 3D inhibits proliferation and migration of papillary thyroid carcinoma by regulating MAPK/ERK signaling pathway - Rui Hai; Qian You; Fei Wu; Guochun Qiu; Qian Yang; Liang Shu; Linjun Xie; Xiangyu Zhou (Molecular Biology Reports, 2022)

The adsorption properties of microporous activated carbon prepared from pistachio nut shell for low-concentration VOCs under low-medium temperatures - Tangying Cheng; Jinjin Li; Xiuwei Ma; Lei Zhou; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2021)

Geographical and temporal variation of multiple paternity in invasive mosquitofish ( Gambusia holbrooki , Gambusia affinis ) - Jiancao Gao; Francesco Santi; Linjun Zhou; Xiaoqin Wang; Rüdiger Riesch; Martin Plath (Molecular Ecology, 2019)
Multiple paternity (MP) increases offspring's genetic variability, which could be linked to invasive species' evolvability in novel distribution ranges. Shifts in MP can be adaptive, with greater MP in harsher/colder environments or towards the end of the reproductive season, but climate could also affect MP indirectly via its effect on reproductive life histories. We tested these hypotheses by genotyping N = 2,903 offspring from N = 306 broods of two closely related livebearing fishes, Gambusia holbrooki and Gambusia affinis . We sampled pregnant females across latitudinal gradients in their invasive ranges in Europe and China, and found more sires per brood and a greater reproductive skew towards northern sampling sites. Moreover, examining monthly sampling from two G. affinis populations, we found MP rates to vary across the reproductive season in a northern Chinese, but not in a southern Chinese population. While our results confirm an increase of MP in harsher/more unpredictable environments, path analysis indicated that, in both cases, the effects of climate are likely to be indirect, mediated by altered life histories. In both species, which rank amongst the 100 most invasive species worldwide, higher MP at the northern edge of their distribution probably increases their invasive potential and favours range expansions, especially in light of the predicted temperature increases due to global climate changes.

Quantitative assessment of enterprise environmental risk mitigation in the context of Na-tech disasters - Ruru Han; Beihai Zhou; Luyang An; Haibo Jin; Lei Ma; Nan Li; Ming Xu; Linjun Li (Environmental Monitoring and Assessment, 2019)

Hypoxia stimulates invasion and migration of human cervical cancer cell lines HeLa/SiHa through the Rab11 trafficking of integrin αvβ3/FAK/PI3K pathway-mediated Rac1 activation - Hao Xu; Yuan Yuan; Wenqian Wu; Min Zhou; Qian Jiang; Linjun Niu; Jiayin Ji; Nianli Liu; Longzhen Zhang; Xia Wang (Journal of Biosciences, 2017)